Impact of soil tillage and land use on soil organic carbon decline under Mediterranean conditions - Basch, G. (2013)
Soils under Mediterranean climate conditions frequently have low to very low levels of soil organic matter (SOM), as a result of low biomass production under the predominantly rainfed conditions and the intensive tillage operations commonly practiced. In order to assess both short and long-term impacts of soil tillage and land use on soil organic carbon, two sets of experiments were performed. One consisted in the identification and soil analysis of 3 pairs of sites under different soil types and land use over 5 to 30 years; in the second experiment a long-term fallow area was repeatedly submitted to different types of soil tillage management (mouldboard plough + disc harrow; non-inversion tine cultivation; no-till) over 3 years. Soil texture, bulk density and SOM were analysed along the whole soil profile in the first experiment, whereas bulk density and SOM to a depth of 30 cm was measured before the first tillage operations and at the end of the observation period in the second experiment. The results clearly indicate that tillage based land use, irrespective of the type of land use, caused a considerable decline in SOM content in the tilled soil layer. Very small and inconsistent differences in SOM between paired soil profiles were observed in the lower part of the profiles. In the second experiment with three types of tillage systems, SOM content decreased with tillage intensity. Avoidance of soil disturbance is an important step towards halting SOM decline under Mediterranean climate conditions.